Regulatory Assessment Toolkit : A Practical Methodology for Assessing Regulation on Trade and Investment in Services - Molinuevo, Martín (Washington, DC: World Bank, 2014)
Regulatory Assessment Toolkit: A Practical Methodology for Assessing Regulation on Services Trade and Investment provides guidance on how to assess and reform the regulatory policies of service trade industries. The toolkit can help government officials evaluate whether their regulatory framework addresses market failures, achieves public interest goals in an efficient manner, and promotes the development of an efficient domestic services market. Depending on the circumstances and the needs of the authorities, the toolkit can serve different purposes, including supporting regulatory reform, improving regulatory governance, negotiating and implementing trade agreements, and streamlining regulations to attract foreign investment. The Regulatory Assessment Toolkit will be of particular interest to policy makers and government officials from regulatory bodies, experts at development banks and donor agencies, and academics and researchers in the field of economic regulation.